Trophic Ecology of Deep-Sea Megafauna in the Ultra-Oligotrophic Southeastern Mediterranean Sea - Guy-Haim, Tamar; Stern, Nir; Sisma-Ventura, Guy (Frontiers in Marine Science, 2022)
The trophic ecology of fourteen species of demersal fishes and six species of demersal decapod crustaceans from the continental slope and rise of the Southeastern Mediterranean Sea (SEMS) was examined using stable isotope analysis. Mean δ13C values among fish species varied by ca. 4.0‰, from -20.85‰ (Macroramphosus scolopax) to -16.57‰ and -16.89‰ (Conger conger and Centrophorus granulosus), showing an enrichment in 13C as a function of depth (200 – 1400 m). Mean δ13C values of the crustaceans showed smaller variation, between -18.54‰ (Aristeus antennatus) and -16.38‰ (Polycheles typhlops). This suggests a shift from pelagic to regenerated benthic carbon sources with depth. Benthic carbon regeneration is further supported by the low benthic-pelagic POM-δ13C values, averaging -24.7 ± 1.2‰, and the mixing model results, presenting relatively low contribution of epipelagic POM to the deep-sea fauna. Mean δ15N values of fish and crustacean species ranged 7.91 ± 0.36‰ to 11.36 ± 0.39‰ and 5.96 ± 0.24‰ to 7.73 ± 0.46‰, respectively, resulting in trophic position estimates, occupying the third and the fourth trophic levels. Thus, despite the proximity to the more productive areas of the shelf, low number of trophic levels (TL~1.0) and narrow isotopic niche breadths (SEAC<1) were observed for demersal crustaceans (TL = 2.94 ± 0.18) and fishes (TL = 3.62 ± 0.31) in the study area – probably due to the ultra-oligotrophic state of the SEMS resulting in limited carbon sources. Our results, which provide the first trophic description of deep-sea megafauna in the SEMS, offer insight into the carbon sources and food web structure of deep-sea ecosystems in oligotrophic marginal seas, and can be further used in ecological modeling and support the sustainable management of marine resources in the deep Levantine Sea.